ASSESSMENT OF THE EFFECTS OF TOP MANAGEMENT COMMITMENT ON ADOPTION OF COMPETITIVE STRATEGIES IN PARASTATALS IN KENYA; A CASE OF KENYA BROADCASTING CORPORATION - Thamaini, Richard; Omwenga, Dr. Jane (European Journal of Business and Strategic Management, 2017)
Purpose: The purpose of this study was to assess the effects of top management commitment on adoption of competitive strategies in parastatals in Kenya. Methodology: The target population of this study was 36 employees in its headquarters in Kenya, the sampling frame of this study was derived from the database of CAK and media council of Kenya which regulates and licenses broadcasters in Kenya, stratified sampling was used in selecting the respondents from their respective management level. Data was collected using questionnaire method, which was self-administered questionnaire. Financial data was obtained from financial statements of KBC records. Multiple regression analysis was used to give an insight into the relationship between factors and competitive strategies. This was done with the help of the statistical package for social sciences (SPSS) version 23.0 for production of graphs, tables, descriptive statistics and inferential statistics. Results: The study established that manager's lack of commitment to performing their roles lead to the low ranks of employees having support and guidance through the strategy implementation process. It can be concluded from this study that when holding other factors constant top management commitment was found to have a positive and significant relationship with strategy implementation. Recommendations: The study recommends that parastatals should urge the top management to be willing to give energy and loyalty to the implementation process strategies because the play a pivotal role in the adoption and implantation process.